Africa's opportunity - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
'The African continent, more than any other, urgently needs agricultural biotechnology, including transgenic crops, to improve food production. African countries need to think and operate as stakeholders, rather than accepting the victim...